DiversePathsJ: diverse shortest paths for bioimage analysis - Uhlmann, Virginie; Haubold, Carsten; Hamprecht, Fred (Bioinformatics, 2018)
Motivation: We introduce a formulation for the general task of finding diverse shortest paths between two end-points. Our approach is not linked to a specific biological problem and can be applied to a large variety of images thanks to its generic implementation as a user-friendly ImageJ/Fiji plugin. It relies on the introduction of additional layers in a Viterbi path graph, which requires slight modifications to the standard Viterbi algorithm rules. This layered graph construction allows for the specification of various constraints imposing diversity between solutions. Results: The software allows obtaining a collection of diverse shortest paths under some user-defined constraints through a convenient and user-friendly interface. It can be used alone or be integrated into larger image analysis pipelines. Availability and implementation: http://bigwww.epfl.ch/algorithms/diversepathsj. Supplementary information: are available at Bioinformatics online.
Gesehen am 31.08.2018
Advance access publication date: 27 September 2017